Antibacterial Effects of Fluoride-Releasing Orthodontic Composites: A Pilot Study - Fırat Öztürk; Ebubekir Toy; Uğur Arslan; Erdem Hatunoğlu (Galenos Yayinevi, 2011)
Aim:The purpose of this study was to evaluate the antibacterial effects of 3 different fluoride-releasing orthodontic composites using a direct contact test (DCT).Materials and Methods:The antibacterial properties of fluoride releasing orthodontic composites were evaluated with the DCT. For the DCT, wells (n=8) of 96-microtitre plates were coated with the tested bonding adhesives [Transbond Plus (3M Unitek, Monrovia, USA) Light Bond (Reliance Ortho Prod. Inc. Itasca, IL, USA) Kurasper F (Kuraray Medical Inc. Okayama, Japan)]. Kalzinol (Zinc-Oxide Eugenol Cement) (Dentsply, Konstanz, Germany was used as a positive control material. A Streptococcus mutans suspension was placed on the surface of each specimen for 1 hour at 37°C. Bacterial growth was monitored for 16 hours with a temperature-controlled microplate spectrophotometer. The kinetics of the outgrowth in each well was recorded continuously at 650 nm every 30 minutes. The data were analyzed by one-way ANOVA, as well as by Tamhane's T2 multiple comparison test. The level of significance was determined as P < 0.05.Results:The evaluation of the results of the DCT revealed that there were statistically significant differences between the four groups (F= 156,951, P= 0.000). The control material (Kalzinol) showed complete inhibition of bacterial growth (mean 0.01 ±0.05). The multiple comparison test indicated that there were no significant difference in bacterial growth between Kalzinol and Transbond Plus (mean 0.12±0.17) (P= 0.509).. Kurasper F (mean 0.73±0.06) and Light Bond (mean 0.85±0.02) showed statistically significant differences (P= 0.000) compared to Kalzinol.Conclusion:Transbond Plus showed marked antibacterial effects.